Pergeseran Konsepsi Kuburan Pada Masyarakat Hindu Bali: Antara Tantra, Calon Arang, dan Wacana Populer - Wirawan, Komang Indra (Jayapangus Press, 2025)
The charnel ground (sĕma/setra) is one of the locations regarded as sacred by the Balinese Hindu community, serving as a center for various religious rituals, ranging from Pitra Yadnya to less common rites such as Ngĕreh. This sacredness is illustrated in the Calon Arang performance, where the charnel ground is featured as one of the key spaces, in addition to being a significant element in the Calon Arang text. On the other hand, various media, from films to information found on the internet, often depict charnel grounds in a negative context. Observing these two contrasting portrayals, this research is aimed at investigating the differences in perception regarding the meaning of charnel grounds from the two aforementioned perspectives, focusing on the discourses surrounding charnel grounds in Calon Arang (both in the text and in performance contexts) and comparing them with narratives disseminated through popular media, while analyzing these through the lens of Balinese Hindu theology rooted in Tantric teachings. The research method employed is a semiotic approach with a descriptive qualitative framework. The findings reveal that contemporary Balinese Hindus tend to hold a negative image of charnel grounds, which is inconsistent with the theological teachings of Hinduism. This shift in perception is largely influenced by widespread information from various popular media, such as social media and the internet, which often portray charnel grounds negatively. As a result, there is a dissonance between the values taught in the Śāstra and the general public's views. Understanding this shift becomes crucial in preserving the theological values of Hinduism amid the flow of digital information. Hence, this study highlights the urgency of awareness regarding this perceptual change and the need for concrete actions to uphold the integrity of religion and culture in Bali.